Lengths in semi-free groups (1988)
Lyndon [3] introduced the idea of a length function on a group in order to give a free product structure for the group in terms of the length function. Work has been done on length functions by Harrison [1], Hoare [2] and others with the objective of studying the structure of groups equipped with length functions.